Bibliometric analysis of scientific literacy using VOS viewer: Analysis of science education. Issue 1 (February 2021) - Effendi, Denti Nanda; Irwandani; Anggraini, Welly; Jatmiko, Agus; Rahmayanti, Henita; Ichsan, Ilmi Zajuli; Mehadi Rahman, Md.
Abstract: Scientific literacy is a person's ability to use scientific knowledge and processes to understand scientific phenomena in solving problems or making decisions. The purpose of this study is to analyze scientific literacy research in the field of physics education and see its trends to find the research opportunity for further research. The results of the bibliometric analysis were used in this study. The search results from the Scopus database was extracted using the VOSviewer software. A total of 644 articles related to scientific literacy were analyzed and mapped. Based on the mapping results, 44 scientific literacy articles in education and 3 scientific literacy articles in physics were obtained. Based on these findings, it can be concluded that scientific literacy related to physics education has been rarely studied. Thus, it can be an opportunity for further researchers to conduct research related to the trends.